2020
DOI: 10.3390/cells9020504
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Based Strategies for Cardiac Reprogramming of Human Mesenchymal Stromal Cells

Abstract: Multipotent adult mesenchymal stromal cells (MSCs) could represent an elegant source for the generation of patient-specific cardiomyocytes needed for regenerative medicine, cardiovascular research, and pharmacological studies. However, the differentiation of adult MSC into a cardiac lineage is challenging compared to embryonic stem cells or induced pluripotent stem cells. Here we used non-integrative methods, including microRNA and mRNA, for cardiac reprogramming of adult MSC derived from bone marrow, dental f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 82 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Another attempt in 2019 found that MSCs derived from adipose tissue can partly be directed towards the cardiac lineage using mod-mRNAs for Gata4, Mef2C, Tbx5 and Mesp1, while cells isolated from bone marrow, and dental follicle demonstrated only weak reprogramming efficiency [238] . Although full maturity of cardiomyocytes could not be reached in the study, the data suggest that adult MSCs can acquire a cardiac-like phenotype and might serve as source for cell replacement strategies in heart regeneration.…”
Section: Mrna In Cellular (Re-)programming – State Of the Artmentioning
confidence: 99%
“…Another attempt in 2019 found that MSCs derived from adipose tissue can partly be directed towards the cardiac lineage using mod-mRNAs for Gata4, Mef2C, Tbx5 and Mesp1, while cells isolated from bone marrow, and dental follicle demonstrated only weak reprogramming efficiency [238] . Although full maturity of cardiomyocytes could not be reached in the study, the data suggest that adult MSCs can acquire a cardiac-like phenotype and might serve as source for cell replacement strategies in heart regeneration.…”
Section: Mrna In Cellular (Re-)programming – State Of the Artmentioning
confidence: 99%
“…Although optimization of mRNA constructs and delivery vehicles are still necessary to introduce such therapies into the clinical practice, they hold great promise as proof-of-concept studies emerge. For instance, cardiac reprogramming of human mesenchymal stromal cells with an mRNA differentiation cocktail has been demonstrated recently [ 38 ]. Similarly, overexpression of human vascular endothelial growth factor A ( VEGFA ) with mRNA promotes endothelial specification of the human ISL1 + progenitors as well as their engraftment, proliferation and survival in vivo [ 39 ].…”
Section: Employing Mrna To Directly Generate or Enhance Therapeutimentioning
confidence: 99%
“…Recent studies have sought to improve the treatment of ischemic heart failure with patient‐derived MSCs by optimizing cardioreparative capacity through co‐instruction with specific cocktails of growth factors; however, this approach remains expensive due to the need for recombinant proteins and represents a significant challenge to scale. This vexing problem prompted researchers led by Atta Behfar (Mayo Clinic, Rochester, Minnesota, USA) to explore an alternative strategy ‐ the induction of enhanced cardiopoiesis (the production of cardiac muscle tissue) by MSCs through targeted gene delivery employing microencapsulated‐modified‐messenger RNA technology 15,16 . In their recent STEM CELLS article, Li et al 11 employed a screening of known mesodermal and pre‐cardiac transcription factors to highlight brachyury expression as a potentially exciting means of engineering a cardiopoietic phenotype in adipose‐derived MSCs.…”
Section: Featured Articlesmentioning
confidence: 99%